Pengaruh Lingkungan Kerja Dan Beban Kerja Terhadap Kinerja Driver Ojol Maxim Di Wilayah Mustika Jaya Kota Bekasi - Enjelya Peronika Lumban Toruan; Tutiek Yoganingsih; Cahyadi Husadha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The importance of effective and ethical human resource management (HRM) is a key factor for a company's success. By adopting a positive attitude and avoiding negative behavior, a company can create a productive and sustainable work environment. A comprehensive HRM approach, from recruitment to employee empowerment, aims not only to organize but also to maximize the positive contributions of the workforce in achieving common goals. The research method used is a quantitative approach with data collection techniques through surveys of Maxim drivers in Mustika Jaya. The data was analyzed using statistical methods to test the relationship between the independent variables, namely the work environment and workload, and the dependent variable, namely the performance of the Maxim ojol driver. The research results show that the work environment and workload have a significant influence on Maxim driver performance. Unsupportive work environment factors, such as conflicts with conventional motorcycle taxi drivers and the lack of supporting facilities, as well as high burdens due to cancellation of work orders by customers, have a negative impact on driver performance. Therefore, the right strategy is needed to improve working conditions and manage workload to support optimizing the performance of Maxim drivers in Mustika Jaya, Bekasi City.